Some Epidemiological Aspects of Cutaneous Leishmaniasis in a New Focus, Central Iran - M. R. Yaghoobi-Ershadi; N. Marvi-Moghadam; R. Jafari; A. A. Akhavan; H. Solimani; A. R. Zahrai-Ramazani; M. H. Arandian; A. R. Dehghan-Dehnavi (Dermatology Research and Practice)
Following the epidemic of cutaneous leishmaniasis in Khatam County, Yazd Province, this study was carried out to determine vector, and animal reservoir host(s) and investigate the human infection during 2005-2006. Four rural districts where the disease had higher prevalence were selected. Sticky paper traps were used to collect sand flies during April to November, biweekly. Meanwhile rodents were captured using Sherman traps from August to November. Households and primary schools were visited and examined for human infection in February 2006. The parasite was detected by RAPD-PCR method. The rate of ulcers and scars among the inhabitants was 4.8% and 9.8%, respectively. Three rodent species were captured during the study: Meriones libycus, Rhombomys opimus, and Tatera indica. Six sand fly species were also collected and identified; among them Phlebotomus papatasi had the highest frequency. Leishmania major was detected as the agent of the disease in the area. It was detected from R. opimus and native people.